2012
DOI: 10.2337/dc11-1483
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Properdin and Enhanced Complement Activation in First-Degree Relatives of South Asian Subjects With Type 2 Diabetes

Abstract: OBJECTIVEEmerging data implicate activation of the complement cascade in the pathogenesis of type 2 diabetes. The objective of the current study was to evaluate the relationships between components of the complement system, metabolic risk factors, and family history of type 2 diabetes in healthy South Asians.RESEARCH DESIGN AND METHODSWe recruited 119 healthy, first-degree relatives of South Asian subjects with type 2 diabetes (SARs) and 119 age- and sex-matched, healthy South Asian control subjects (SACs). Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…Recently, elevated plasma levels of properdin and factor B were found in subjects at risk of developing type 2 diabetes [20] . This is consistent with a role for the alternative pathway in NASH, since insulin resistance is an independent risk factor for NASH [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, elevated plasma levels of properdin and factor B were found in subjects at risk of developing type 2 diabetes [20] . This is consistent with a role for the alternative pathway in NASH, since insulin resistance is an independent risk factor for NASH [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Complement is the critical part of the innate immunity system that identifies pathogens and damaged cells, which initiates the phagocytosis and proinflammatory responses. Elevated complement proteins in circulation of patients with diabetes have been considered as strong predictors of the development of diabetes and related complications . Although brain was traditionally considered as an immune‐privileged organ, it has been recently recognized that neuronal cells in the CNS could synthesize many complement system components, which maintain immunosurveillance and biological activities in the brain .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated complement proteins in circulation of patients with diabetes have been considered as strong predictors of the development of diabetes and related complications. 11 Although brain was traditionally considered as an immune-privileged organ, it has been recently recognized that neuronal cells in the CNS could synthesize many complement system components, which maintain immunosurveillance and biological activities in the brain. 12,13 Specifically, complement component 3 (C3), the critical central component of three complement cascades, 14 not only mediates the synaptic pruning and synaptic refinement during brain development, 15 but also exerts detrimental effects on the CNS in the adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 It has been shown that properdin deficiency results in an increased risk of infection; infection mortality rates of 33%-75% have been reported. 36 It has been hypothesized that higher levels of properdin, such as the levels shown in our AMR cohort, result in a higher capacity to activate the alternative pathway and may therefore represent activation of the alternative pathway in relevant situations, such as cardiovascular events, 37 type 2 diabetes mellitus, 38 and AMR. Human studies on the alternative pathway factor properdin in relation to transplantation are scarce.…”
Section: Increased Risk Of Amr In Patients With Pasn428 (P¼) In Cfp mentioning
confidence: 94%